Ethnobotanical, ethnopharmacological and pharmacology of the species Acanthaceae, Aizoaceae, Alismataceae e Amaranthaceae - Oliveira, Geysse Kelle de (2019)
The present work aimed to achieve through a bibliographic review an information survey ethnobotany, ethnopharmacological and pharmacology informations of the family-owned species Acanthaceae, Aizoaceae, Alismataceae e Amaranthaceae, cultivated in the Medicinal Garden of Campus 2 from Universidade Paranaense - UNIPAR, located in the county of Umuarama - PR. For this purpose, it was used the following database:  Medline, PubMed, Scielo and Academic Google, where were searched the following key-words: ethnobotany and ethnopharmacology. Medicinal plants, popular use pharmacological action, chemical composition, adverse effects, besides the scientific names of the species. The four families approached in this study added 14 species, being most of them (11 species) of medicinal use, with ethnobotanical and ethnopharmacological informations registered in the consulted literature. However, only 5 species presented pharmacological studies proving the popular uses. And, only 3 species have exclusively ornamental use.